Young people with type 1 diabetes mellitus: Attitudes, perceptions, and experiences of diabetes management and continuous subcutaneous insulin infusion therapy. Issue 3 (4th January 2017) - Perry, Lin; James, Steven; Steinbeck, Katharine; Dunbabin, Janet; Lowe, Julia
Abstract: Rationale, aims, and objectives: Continuous subcutaneous insulin infusion (CSII; insulin pump) use is increasing. However, there is little information about how this technology is used compared with other insulin delivery methods (ie, injections) by young people with type 1 diabetes mellitus in Australia. This study explored young people's attitudes, perceptions, and experiences with diabetes management comparing those using with those not using CSII, and proportions likely to transition to adult services requiring initiation and/or support for CSII use. Methods: A survey was undertaken of young people (aged 12 to 18 years) with type 1 diabetes mellitus and their parents/guardians living in Hunter New England, Australia, using a questionnaire designed to collect quantitative, descriptive, and demographic data. Most questions were based on previously developed and validated instruments. In total, 107 respondents returned partially or fully completed questionnaires. Results: Respondents had positive attitudes and perceptions of their self‐efficacy and diabetes management, but were moderately disturbed by their diabetes and reported experiencing suboptimal management outcomes. Patterns of associations were demonstrated between knowledge, attitudes, and experiences of diabetes modeled by regression analysis. There were no statistically significant differences in responses between users and nonusers of CSII. Over 40% indicated their intention to use the technology as adults. Conclusions: Opportunities for enhanced diabetes service support were clear, and CSII did not appear to be used to its full potential. Service redesign could enhance support for this young population using all preferred insulin delivery methods and should align to patients' goals and preferences to maximize service and patient gain.